2007
DOI: 10.1677/joe-07-0161
|View full text |Cite
|
Sign up to set email alerts
|

Rat insulin promoter 2-Cre recombinase mice bred onto a pure C57BL/6J background exhibit unaltered glucose tolerance

Abstract: b-Cell-specific gene targeting is a widely used tool when studying genes involved in b-cell function. For this purpose, several conditional b-cell knockouts have been generated using the rat insulin promoter 2-Cre recombinase (RIP2-Cre) mouse. However, it was recently observed that expression of Cre alone in b-cells may affect whole body glucose homeostasis. Therefore, we investigated glucose homeostasis, insulin secretion, and b-cell mass in our line of RIP2-Cre mice bred onto the C57BL/6J genetic background.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 12 publications
4
34
1
Order By: Relevance
“…A beta cell-specific KO of HSL (beta HSL KO) was created by Cre-mediated recombination (rat insulin 2 promoter [RIP2] Cre mouse) [31][32][33] in the beta cells of a transgenic mouse with LoxP sites flanking exons 2 to 7 in Hsl (also known as Lipe) [20]. In the present study, we show that a beta cell-specific loss of HSL results in hyperglycaemia due to impaired insulin secretion.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…A beta cell-specific KO of HSL (beta HSL KO) was created by Cre-mediated recombination (rat insulin 2 promoter [RIP2] Cre mouse) [31][32][33] in the beta cells of a transgenic mouse with LoxP sites flanking exons 2 to 7 in Hsl (also known as Lipe) [20]. In the present study, we show that a beta cell-specific loss of HSL results in hyperglycaemia due to impaired insulin secretion.…”
Section: Introductionmentioning
confidence: 68%
“…However, we have been unable to detect any expression of Cre in the hypothalamus of our beta HSL KO mouse (data not shown). In addition, we have investigated glucose homeostasis and insulin secretion in vivo and in vitro in our line of RIP2 Cre mice [33]; no differences between transgenic and WT mice were found. We were thus unable to replicate previous findings [48].…”
Section: Discussionmentioning
confidence: 99%
“…The 5-exon deletion is lacking from the C57BL/6N strain that we use (Fex et al 2007b), which was derived from the one kept at the NIH Animal Genetic Resource, and embryo-derived into Taconic's facility; C57BL/6J mice are also available from the Jackson Laboratory, and these were used in the studies on NNT (Toye et al 2005).…”
Section: Mitochondrial Dysfunction In C57bl/6j Micementioning
confidence: 99%
“…However, we did not detect significant changes in desnutrin expression in hypothalamus, even when desnutrin expression was 80% lower in islets upon mating of desnutrin floxed mice with RIP-Cre mice. Nor did we detect impaired glucose/insulin homeostasis in our control RIP-Cre mice, probably due to the relatively young age of mice (8 weeks) and their pure C57BL/6 background, as previously reported (Fex et al, 2007). In addition, temporal ablation of desnutrin only in adult stage by RIP-CreER (Liu et al, 2010) confirmed the phenotype of our bKO mice using RIP-Cre mice.…”
Section: Discussionsupporting
confidence: 83%
“…In this regard, impairment in insulin secretion in RIP-Cre mice has been described in some reports (Lee et al, 2006). On the other hand, others have reported unaltered glucose tolerance in RIP-Cre mice when bred onto a pure C57BL/6 background (Fex et al, 2007). In our studies, control RIP-Cre mice did not show any impairment in insulin secretion and had the same glucose and insulin tolerance as floxed mice.…”
Section: Desnutrin Ablation In Pancreatic B Cells Causes Glucose Intosupporting
confidence: 66%